First detection of low field microwave absorption in the disordered multiferroic double perovskite BiFe0.5Mn0.5O3. (15th June 2021) - Sibanda, Brian; Mahule, Tebogo Sfiso; Delmonte, Davide; Sala, Andrea; Gilioli, Edmondo; Srinivasu, V V
Abstract: BiFe0.5 Mn0.5 O3 (BFMO) is an intriguing magnetic double perovskite, only obtainable through high pressure-high temperature synthesis. It shows bulk multiferroic properties, namely the coexistence between a spin canted antiferromagnetic structure superimposed to an externally induced electric polarization at least from 77 K. In particular, the system is characterized by a significant weak ferromagnetic hysteresis loop and by a very rare phenomenon: the spontaneous magnetization reversal (MRV) versus temperature in the low field regime. To clarify the BFMO exotic magnetic phase in the low field regime, the Electron Spin Resonance (ESR) and the low field microwave absorption (LFMA) techniques were used, providing the first observation of LFMA in the bulk BFMO as an additional functionality of this material. A striking feature is that the hysteresis in LFMA signals vanishes above 45 K, while the bulk M-H loop hysteresis, measured in the same field range of LFMA, persists till room temperature. The temperature at which LFMA hysteresis vanishes qualitatively matches the position of the magnetic susceptibility's second derivative peak, corresponding to the temperature at which the local second order mechanism responsible for MRV is maximum. The line shape of LFMA completely changes above 45 K and the ESR linewidth starts decreasing above this temperature, indicating the role of defect/disorder induced inhomogeneity. The temperature evolution of LFMA hysteresis and line shapes as a measure of the competition between Fe- and Mn-rich clusters suggests a sort of local frustration at the microscopic scale, responsible for the peculiar magnetization reversal of this system.